The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1645/ge-182r
|View full text |Cite
|
Sign up to set email alerts
|

Uncinaria hamiltoni (Nematoda: Ancylostomatidae) in South American Sea Lions, Otaria flavescens, From Northern Patagonia, Argentina

Abstract: Thirty-one South American sea lion pups (Otaria flavescens) found dead in Punta León, Argentina, during the summer of 2002, were examined for hookworms (Uncinaria hamiltoni). Parasite parameters were analyzed in 2 locations of the rookery, i.e., a traditional, well-structured breeding area and an expanding area with juveniles and a lax social structure. Prevalence of hookworms was 50% in both localities, and no difference was observed in prevalence between pup sexes (P Ͼ 0.05). Hookworms were concentrated in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…All hookworms appeared to be of a similar size and were apparently reaching patency at about the end of P1 indicating a highly synchronised time of infection. (Sepúlveda and Alcaíno 1993), Lyons et al (2000a), and(Berón-Vera et al 2004) observed a similar tight profile of developmental stage that they suggested was supportive of the hypothesis of transmammary infection. Another argument in favour of this hypothesis was that faeces of pups treated once with an anthelmintic drug at birth were negative until the end of the study.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…All hookworms appeared to be of a similar size and were apparently reaching patency at about the end of P1 indicating a highly synchronised time of infection. (Sepúlveda and Alcaíno 1993), Lyons et al (2000a), and(Berón-Vera et al 2004) observed a similar tight profile of developmental stage that they suggested was supportive of the hypothesis of transmammary infection. Another argument in favour of this hypothesis was that faeces of pups treated once with an anthelmintic drug at birth were negative until the end of the study.…”
Section: Discussionsupporting
confidence: 54%
“…In the latter studies, pups in good body condition had more hookworms in their intestines than those in poor body condition. Assuming that transmammary transmission is the only way for pups to become infected and that hookworm burden is proportional to the quantity of milk ingested soon after birth, it is then reasonable to assume that pups in good body condition will have received more milk and, therefore, a greater amount of infective larvae (Lyons et al 1997(Lyons et al , 2001Berón-Vera et al 2004). Although there were significantly more males directly killed by hookworm infection than females, the burden in NZSL pups did not vary between sexes.…”
Section: Discussionmentioning
confidence: 99%
“…from NZSL were similar to those from Berón-Vera et al (2004), but were reduced relative to U. lucasi and U. hamiltoni as described by Baylis (1933Baylis ( , 1947. Almost all variables measured in hookworms from the southern hemisphere (Botto and Mañé-Garzón 1975;Berón-Vera et al 2004) present a broad range with regard to measurements important for comparing species: buccal capsule length, esophagus length, distance of vulva to posterior end, spicule length, and egg dimensions (Table 1). Disparity in the size of mature hookworms within the same host was observed during the present study.…”
Section: Discussionsupporting
confidence: 66%
“…from NZSL pups, U. hamiltoni from Otaria byronia(Baylis 1933), U. lucasi from C. ursinus(Baylis 1947) and U. hamiltoni from Otaria flavescens(Berón-Vera et al 2004) …”
mentioning
confidence: 99%
“…Despite these reports, there have been no comprehensive systematic studies of hookworms from pinnipeds. Literature reports have either diagnosed hookworms as Uncinaria sp., assigned specimens to one of the two described species (Berón-Vera et al, 2004), or noted that specimens do not fit the description of known species (Dailey and Hill, 1970;Castinel et al, 2006). This potential underestimation of species diversity has led to the suggestion of broad host ranges for U. lucasi and U. hamiltoni.…”
Section: Discussionmentioning
confidence: 99%